(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This study handles the methodological Standards to evaluate the relation of the research title, its queries, its importance and its targets with the problem of the research in asample of Doctorate Thesis accomplished in Sociology Department, due to the necessity of commitment to the methodological basis in elaborating the outcomes of the academic research to promote the scientific knowledge, modernize and develop societies. The analytical descriptive method was used in this study, and the critical analysis method. The importance of this study lies in the importance of commitment to the necessary methodological standards to form the research title, its queries, and to identify the importance and the sought targets of implementing it in a way that fits the nature of the research problem. It aims at demonstrating the relation between the title of the research, its queries, its importance and its targets with the problem of the research. It concluded that : the titles of 60% of the Thesis’ titles of the research sample were absolutely related to the research problem, and the title of 40 % of the thesis’ titles is linked to the research problem, and some researchers did not recognize the difference between the questions of the research and its hypotheses, and put them under the title of the research’s queries, and the percentage of 60 % of the research’s sample has added one side of the research’s scientific importance, and the percentage of 40% of the research sample’s thesis, has added completely.